An overview of thorium as a prospective natural resource for future energy - Jyothi, Rajesh Kumar; De Melo, Leonardo Gadelha Tumajan Costa; Santos, Rafael M.; Yoon, Ho-Sung (Frontiers in Energy Research, 2023)
Thorium is a naturally occurring radioactive element that has been identified as a potential alternative fuel for nuclear energy production. Additionally, thorium-based nuclear reactors have inherent safety features that reduce the risk of nuclear accidents and proliferation. As a result, there has been growing interest in the development of thorium-based nuclear energy as a viable alternative to fossil fuels. This paper looks at the present status of thorium nuclear fuel technology, providing an overview of thorium as a prospective natural resource for future energy, the global availability of mineral supplies, and discusses the technical, economic, and environmental factors that may influence its implementation. Potential advantages and challenges critical to further development associated with thorium-based nuclear energy are highlighted as well, and an outlook on its future prospects is provided. Thorium offers advantageous physical and chemical properties over uranium, has a higher energy density, and produces less waste, in addition to its greater natural abundance, making it to be considered a “future nuclear fuel”. There are concerns about the cost and scalability of thorium-based nuclear energy, with uncertainty around the cost to develop, build, and operate thorium reactors, as it has not yet been demonstrated in large-scale commercial reactors—although almost all current reactor types have been built and run using thorium—as it is the case with Uranium-based nuclear technology—the dominant form of nuclear energy for over half a century, having received much more investment and attention than thorium-based technology. Thorium has the potential to contribute towards a more sustainable nuclear industry, including lower lifecycle emissions and more efficient resource utilization, but for this, an acceleration of efforts to date is needed to ensure that this becomes an important climate change stabilizing wedge by the mid-21st century.